(untitled) (Advances in Military Technology, 2023)
This paper presents the results of summarizing the algorithm of target selection and changing guidance law applied for medium and long-range air-to-air intercept missiles to ensure the ability to detect and distinguish the group-separating target, which in turn improving the efficiency in tracking and terminating the selected targets. The proposed algorithm reduces the miss distance to a minimal value while ensuring two primary requirements, including distinguishing each target in the group by Doppler frequency and identifying the flight direction of the target to track and destroy.